Gold catalyzed glycosidations for the synthesis of sugar acrylate/acrylamide hybrids and their utility - Thadke, Shivaji A.; Kar, Mritunjoy; Sen Gupta, Sayam; Hotha, Srinivas (Carbohydrate Research, 2011)
Propargyl glyco 1,2-orthoesters were exploited for the efficient synthesis of interesting glycomonomers such as glyco-acrylates and acrylamides using gold catalysts. It was observed that propargyl glyco 1,2-orthoesters with hydroxyethyl acrylates gives very good yield of the corresponding glyco-acrylates in a single step in the presence of catalytic amount of gold(III) catalyst; whereas, gold catalyzed glycosidation reaction on hydroxyethyl acrylamides was found to yield the corresponding acrylamidoyl 1,2-orthoester which was then converted to the corresponding glycol-acrylamide in the presence of catalytic amount of TMSOTf. Synthesized glyco-acrylate/acrylamide monomers are shown to undergo thiolate addition as well as free radical polymerization (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Glycoacrylamides; Glycoacrylates; Glycopolymers; glycosylation; Gold